อิทธิพลของสมรรถนะโซ่อุปทานในฐานะปัจจัยคั่นกลางที่ส่งผลต่อกลยุทธ์การพัฒนาผลิตภัณฑ์ นวัตกรรม และความสามารถทางการแข่งขันของอุตสาหกรรมการผลิตชิ้นส่วนยานยนต์ของไทย - กันนุลา อาจหาญ; จารุพัฒน์หิรัญ ศุภสิทธิ์; มีใจซื่อ ประยงค์ (Ph.D. in Social Sciences Journal, 2017)
อิทธิพลของปัจจัยคั่นกลางต่อความสามารถทางการแข่งขันและสมรรถนะโซ่อุปทานของอุตสาหกรรมการผลิตชิ้นส่วนยานยนต์ไทยเป็นงานวิจัยเชิงสำรวจโดยมีวัตถุประสงค์ (1) เพื่อศึกษาอิทธิพลปัจจัยคั่นกลางได้แก่ความคล่องตัว การปรับตัว และความเท่าเทียมกันต่อความสามารถทางการแข่งขันและสมรรถนะโซ่อุปทานของอุตสาหกรรมผลิตชิ้นส่วนยานยนต์ไทย (2) เพื่อศึกษาความสัมพันธ์และอิทธิพลปัจจัยอันได้แก่กลยุทธ์ การพัฒนาผลิตภัณฑ์และนวัตกรรมต่อความคล่องตัว การปรับตัวและความเท่าเทียมกันของโซ่อุปทานอุตสาหกรรมผลิตชิ้นส่วนยานยนต์ไทย โดยเก็บข้อมูลจากผู้บริหารที่เกี่ยวข้องโดยตรงกับการบริหารโซ่อุปทานของผู้ประกอบการผลิตชิ้นส่วนยานยนต์ตั้งแต่ระดับที่ 2 (Tier2) งานวิจัยนี้ใช้มาตรวัดความสามารถทางการแข่งขันและสมรรถนะโซ่อุปทานขององค์กรโดยการใช้แบบสอบถามพหุปัจจัยความสามารถทางการแข่งขันและแบบสอบถามวัดระดับสมรรถนะโซ่อุปทานตามระบบ SCOR ในการเก็บรวบรวมข้อมูล เพื่อยืนยันในเชิงปริมาณทำการวิเคราะห์ข้อมูลหาค่าสถิติพื้นฐานด้วยโปรแกรมสำเร็จรูปข้อมูลสถิติที่ใช้ได้แก่ ความถี่ค่าเบี่ยงเบนมาตรฐาน การวิเคราะห์เส้นทางและวัดความกลมกลืนของแบบจำลองโครงสร้างกับข้อมูลเชิงประจักษ์โดยใช้สมการโครงสร้าง (SEM) ได้ผลการวิเคราะห์อิทธิพลปัจจัยคั่นกลางต่อความสามารถทางการแข่งขันมีค่า CMIN=214.465, CMIN/DF=10.95,P-Value=0.01, GFI=0.956และAGFI=0.853 และผลการวิเคราะห์อิทธิพลของปัจจัยคั่นกลางต่อสมรรถนะมีค่าCMIN=214.644ค่าCMIN/DF=10.998,P-Value=0.001,GFI=0.960และAGFI=0.856 THE INFLUENCE OF SUPPLY CHAIN CAPABILITY AS THE INTERMEDIATE FACTORS AFFECTED TO THE STRATEGY, PRODUCT DEVELOPMENT, INNOVATION AND ABILITY OF COMPETTITIVENESS OF THAI AUTOMOTIVE PARTS MANUFACTURING The influence of the intermediate factors on the competitiveness and capability of the supply chain, manufacturing, automotive parts, Thailand applied by a Survey Research. The objectives to study on (1) to study the influence of factors, including intermediate agility, adaptability and alignment. The competitiveness and capability of the supply chain industry, automotive components, Thailand. (2) to study the relationship and the influence of factors such as strategies, products development, the innovative on agility, adaptability and alignment of the supply chain automotive parts’ industry of Thailand. By collecting data from all executives who are involving in supply chain of automotive parts manufacturing industry in Thailand. They are managing level at the level of second tier or above in Thailand. This research is used to measure the competitiveness of the enterprise and supply chain capability by applying a Multi-factor questionnaire in terms of competitiveness, the Assessment questionnaire to measure the level of supply chain performance based on SCOR system. The data collections to confirm quantitatively. The analysis done with descriptive statistics and data processing to evaluate by Statistical Package program. The Statistics applied through the Frequency, Standard Deviation, Path Analysis and Harmonized Statistical measurable of the structural model with empirical data. The SEM analysis appeared that the result of the factors influencing the competitiveness on the supply as the value of CMIN=214.46, CMIN/DF=10.95, P-Value=0.01, GFI=0.956 and AGFI=0.853.The analysis of factors influencing the capability of the supply chain as the CMIN=214.644, CMIN/DF=10.998, P-Value=0.001, GFI=0.960 and AGFI=0.856.